Development of a Model of Intention to Adopt Electric Motorcycles in Indonesia - Tasya Santi Rahmawati; Yuniaristanto Yuniaristanto; Wahyudi Sutopo; Muhammad Hisjam (Universitas Muhammadiyah Magelang, 2022)
Indonesia's economic sector continues to rely on carbon-emitting fossil fuels. The government is speeding up electrification by encouraging people to switch from traditional to electric automobiles. Electric motorcycles are one option for lowering CO2 emissions. Many researchers have investigated the value attributes affecting consumers’ attitudes and behavior around electric motorcycles. The structural model was created using the Partial Least Square ”“ Structural Equation Model (PLS-SEM). The questionnaires were circulated through the internet, and 1,223 valid responses were received. Researching people's interest in environmentally friendly vehicles and the growing ecosystem of electric vehicles will indicate that the electric motorcycle business has a bright future. This research also shows that attitude is a major impact on electric motorcycle purchase intention and infrastructure, and subjective norms and perceived behavioral control have a direct effect on electric motorcycle purchase intention. Cost and technology do not influence a person in determining his desire to buy an electric vehicle.